The Use of Picture Word Cards Through Mother Tongue Approach to Improve Reading Literacy in Second Grade of Watumite Ende Catholic Elementary School - Bebhe, Agustina; Vianey Sayangan , Yohanes; Partisia Wa’u, Maria; Qondias, Dimas (Perspektif Pendidikan dan Keguruan, 2024)
This study aims to improve reading literacy skills using picture word card media through the mother tongue approach in grade II students at Watumite Ende Catholic Elementary School. The subjects of this study, which was taken by researchers, were grade II students, totaling 17 students, while the object of this study was reading literacy skills. This study has four stages: planning, action implementation, observation, and reflection. Researchers use the class action method (PTK) to collect data. Data was collected using picture word card media through the mother tongue approach. Based on the research data and discussion, the research can be concluded that the use of picture word card media through the mother tongue approach can improve students' reading literacy skills in Indonesian language learning in class II of Watumite Ende Catholic Elementary School.